A Case Study on Intelligent Service Design in Ubiquitous Computing - Chang, Hangbae; Kwon, Hyukjun; Kang, Jonggu; Kim, Yanghoon (COMPUTING AND INFORMATICS, 2012)
In this study we designed the killer services for the scene of labor learning in ubiquitous computing. To achieve this study, we have explored the unmet needs of teachers in the scene of labor learning and examined whether the unmet needs could be served by the resources and capabilities of ubiquitous computing. Then, we have crafted a detail killer services for the scene of labor learning proposed to serve educational users with the service architecture. The result of this study will be applied to develop new business model in ubiquitous computing as the basic research.